Ductal Flow Ratio as Measure of Transition in Preterm Infants After Birth: A Pilot Study - Brouwer, Emma; Knol, Ronny; Hahurij, Nathan D.; Hooper, Stuart B.; Te Pas, Arjan B.; Roest, Arno A. W. (Frontiers in Pediatrics, 2021)
Background: Cardiovascular changes during the transition from intra- to extrauterine life, alters the pressure gradient across the ductus arteriosus (DA). DA flow ratio (R-L/L-R) has been suggested to reflect the infant’s transitional status, and could potentially predict neonatal outcomes after preterm birth. Aim: Determine whether DA flow ratio correlates with oxygenation parameters in preterm infants at 1 hour after birth. Methods: Echocardiography was performed in preterm infants born <32 weeks gestational age (GA), as part of an ancillary study. DA flow was measured at 1 hour after birth. DA flow ratio was correlated with FiO2, SpO2 and SpO2/FiO2 (SF) ratio. The DA flow ratio of infants receiving physiological-based cord clamping (PBCC) or time-based cord clamping (TBCC) were compared. Results: Measurements from 16 infants were analysed (median [IQR] GA 29 [27-30] weeks; birthweight 1176 [951-1409] grams). R-L DA shunting was 16 [17-27] ml/kg/min and L-R was 110 [81 – 124] ml/kg/min. The DA flow ratio was 0.18 [0.11-0.28], SpO2 94 [93-96]%, FiO2 was 23 [21-28]% and SF ratio 4.1 [3.3-4.5]. There was a moderate correlation between DA flow ratio and SpO2 (correlation coefficient (CC) -0.415; p=0.110), FiO2 (CC 0.384; p=0.142) and SF ratio (CC -0.356; p=0.175). There were no differences in DA flow measurements between infants where PBBC or TBCC was performed. Conclusion: In this pilot study we observed a non-significant positive correlation between DA flow ratio at 1 hour after birth and oxygenation parameters in preterm infants.